Assessing the Lasting Impact of Co-Curricular Service Learning in Undergraduate Chemistry - Cruz, David Jonathan L (Archīum Ateneo, 2024)
Existing research primarily examines the impact of structured, credit-bearing service learning in undergraduate chemistry, leaving the potential contributions of co-curricular service learning and its lasting influence on chemistry graduates underexplored. Therefore, this mixed-methods study aimed to assess the lasting impact of co-curricular service learning in undergraduate chemistry by conducting a longitudinal follow-up of past Kimikamahika volunteers and their peers who were not part of this community outreach. Kimikamahika stands for a magical show in chemistry wherein volunteers from a campus organization do a live demonstration of chemistry experiments to a variety of audiences in order to spark an interest in science. A total of 78 participants joined this study, with 54 in the volunteer group and 24 in the comparison group. The findings revealed that co-curricular service learning in undergraduate chemistry, such as Kimikamahika, can help students develop course-related skills, appreciate the real-world application of chemistry, recognize career opportunities, strengthen leadership skills, and deepen community engagement as they seek to address underachievement in science as a social problem. These gains from co-curricular service learning are more evident if students organize the community outreach and render a total of at least 10 h of community engagement. Such findings can inform higher education institutions and educators on how to design effective service learning experiences within and outside the undergraduate chemistry curriculum.